The Effects of ICT Towards Students’ Attitude - Wan Elisa Wan Hoesni; Fatin Nabilah Abu Hassan; Muhammad Talhah Ajmain; Nurul Atika Mohd Rosli (Khazanah Pendidikan Islam, 2020)
Advancement of Information and communication technology (ICT) rapidly transform many sectors and it does give and impact also to the educational field. Ministry of Education Malaysia starts to plan the curriculum to include ICT and teacher starts exploring different method and teaching style to develop students higher order thinking skills. Teacher plays an important role in designing lesson to integrate ICT as it will give effect to students’ attitude in learning. The purpose of this study is to determine the effects of ICT towards students’ attitude. The methodology of study utilized a systematic document analysis technique where issues related to effect ICT towards student attitude which have given impact to the teachers’ and students’ behavior in the form of any reference are analyzed. SAMR model will show that there is different level of degree of ICT integration that teacher can use and implement in class. Results shows that when ICT is use in class it will give an advantage in terms of student performances, motivation and efficiency. The student and classroom environment itself will be dynamic, active listening, collaborative learning, interactivity and communication will take place. Maximizing ICT potential can create and enhance learning to take place more effectively and transforming from teacher-centered to student-centered learning which are in line with the 21st century goals.